Enhancing Muslim studies of other religions through digital technologies - Ibrahim, Haslina; Mat Zain, Aemy Elyani; Ismail, Safinah; Ismail, Nazneen; Abu Hassan, Nur Aisyah; Fatin Farzana, Dass Meral (IIUM, 2025)
Digital technologies have fundamentally transformed contemporary lifestyles and have significantly impacted both formal and informal learning. The study of religions, without exception, must leverage digital technologies to enhance its societal roles and impact. This paper therefore explores the possibility of adopting an innovative approach in Muslim scholarship on religions by introducing the use of digital applications in the study of other religions, a vital sub-discipline of Usuluddin. Additionally, the paper examines how digital technologies can foster a more inclusive approach to understanding diverse religious perspectives thereby promoting positive inter-religious dialogue and meaningful engagement. Through qualitative interviews with experts in religious studies, this paper presents their insights and recommendations on the conceptualisation of the digital application. Based on these findings, the paper argues for a symbiotic relationship between the traditional approaches and digital technologies. This integration is essential not only to maintain the relevance of Muslim studies on other religions in the digital age but also to advocate for interreligious understanding, which is instrumental in achieving social harmony